ANALISIS PENDAPATAN PETERNAK AYAM BROILER PADA POLA KEMITRAAN YANG BERBEDA DI KECAMATAN PAYAKUMBUH TIMUR (Studi Kasus PT. Karya Semangat Mandiri (KSM) dan Poultry Shop Torang) (Analysis of Broiler Chicken Income in Different Partnership Patterns in East Payakumbuh District (Case Study of PT. Karya Semangat Mandiri (KSM) and Poultry Shop Torang)) - Ali Makmur; Maryega Antoni; Arfa’i Arfa’i; Rahmi Wati (Jurnal Ilmu dan Teknologi Peternakan, 2020)
This study aimed to determine the partnership pattern and the income of broiler breeders partnering with PT. Karya Semangat Mandiri (KSM) and Torang Poultry Shop in East Payakumbuh District. The census method was used in this study through a survey method and direct observation in the field using a questionnaire involving 12 broiler breeders who partnered with PT. KSM and ten broiler breeders partnered with Torang Poultry Shop. Descriptive qualitative and quantitative analyses were used to analyze the data by observing the patterns and calculating the costs, income, and revenues. The results of the study indicated that the breeders partnered with PT. KSM adopted a plasma core partnership pattern with a written agreement, and the farmers were required to place a security deposit to the company. The farmer who partnered with Torang Poultry Shop used a profit-sharing pattern in which the benefits were equally shared. The agreement was not in written form, and the farmers did not provide a security deposit. The income of farmers partnered with PT. KSM was higher compared to income of the farmers partnered with the Torang Poultry Shop